PEMEROLEHAN KOSAKATA DASAR NOMINA BAHASA INDONESIA ANAK USIA 3 TAHUN (STUDI KASUS DI KELURAHAN LEBAK BANDUNG KOTA JAMBI) - Andi Hani; Ade Rahima; Abdoel Gafar (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research is aimed at identifying the acquisition of basic noun vocabulary of Indonesian language on 3 years old childern in Lebak Bandung area. Thsi research is qualitative descriptive. In conducting the data, the question answer technique is used by showing pictures to 3 years old children in Kelurahan Lebak Bandung. Based on the result of the research, it can be found that 3 years old children are able to pronounce one to six vocabulary which categorize good and less good with their own words.  Keywords : Acquisition, Indonesian Language Noun, 3 Years Old Children